Pengaruh Mekanisme Good Corporate Governance dan Profitabilitas Terhadap Praktik Manajemen Laba pada Perusahaan Perbankan Periode 2017-2021 - Adinda Shava Rahmadani; Gendro Wiyono; Alfiatul Maulida (Universitas Batanghari Jambi, 2023)
The actions taken by PT Envy carried out earnings management for fraudulent financial statements and consolidated its subsidiary companies so that investors became wary of investing their shares, thus this research was conducted to determine the effect of good corporate governance mechanisms and profitability on earnings management practices. Good corporate governance in this study uses institutional ownership and managerial ownership.This study used a population of 43 from banking companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2021 period with non-probability sampling, and a purposive sampling technique with certain criteria so as to get a sample that met the sample criteria of 8 companies. This type of research is quantitative, so that the collection of research data uses secondary data in the form of financial reports officially issued by the IDX www.idx.co.id. Earnings management is measured using discretionary accruals, institutional ownership is measured by KI, managerial ownership is measured by KM, and profitability is measured by ROA. The analytical method used is descriptive analysis test, classical assumption test, multiple linear regression and hypothesis testing. The results of this study indicate that institutional ownership and profitability have no effect on earnings management practices, while managerial ownership has an effect on earnings management practices. Simultaneously profitability, institutional ownership, and managerial ownership affect earnings management practices